Preposteryjność sytuacji przestrzennej w "Ziarnie prawdy" Zygmunta Miłoszewskiego = The preposterity of the spatial situation in "The Grain of Truth" by Zygmunt Miłoszewski - Rosiński, Cezary (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article presents the issue of spatial situation founded on the category of preposterity in "Ziarno prawdy" ["The Grain of Truth"] by Zygmunt Miłoszewski. While using the term "preposterity" proposed by Mieke Bal, the author of this article examines the mutual space conditions between literature and non-textual reality and describes the relationship between works of art in the historical process. Also, terms such as "heterotopy" by Michel Foucalt "duality of the culture of meaning" and "the culture of presence" by Hans Ulrich Gumbrecht are being employed in line with the set art aims."
Keywords: preposteryjność; uważność; sytuacje przestrzenne; kultura obecności; preposterity; attentiveness; spatial situation; culture of presence